2018
DOI: 10.1371/journal.pone.0204871
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of GTP-cyclohydrolase 1 gene in Plasmodium falciparum isolates with the quadruple mutant of dihydrofolate reductase and dihydropteroate synthase genes in Ghana

Abstract: Sulfadoxine-pyrimethamine (SP) is used as malaria chemoprophylaxis for pregnant women and children in Ghana. Plasmodium falciparum resistance to SP is linked to mutations in the dihydropteroate synthase gene (pfdhps), dihydrofolate reductase gene (pfdhfr) and amplification of GTP cyclohydrolase 1 (pfgch1) gene. The pfgch1 duplication is associated with pfdhfr L164, a crucial mutant for high level pyrimethamine resistance which is rare in Ghana. The presence of amplified pfgch1 in Ghanaian isolates could be an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
3
16
1
Order By: Relevance
“…In this study, an association between pfgch1 gene multiple copy number and the pfdhfr-I164L mutation was also observed. However, in Ghana with low level of pfgch1 gene amplification (6%; 12/192), no dhfr-I164L was detected in samples with amplified pfgch1 [30]. The positive correlation between pfdhps (540E) and pfgch1 multiple copies observed in this study was not observed before.…”
Section: Discussioncontrasting
confidence: 72%
“…In this study, an association between pfgch1 gene multiple copy number and the pfdhfr-I164L mutation was also observed. However, in Ghana with low level of pfgch1 gene amplification (6%; 12/192), no dhfr-I164L was detected in samples with amplified pfgch1 [30]. The positive correlation between pfdhps (540E) and pfgch1 multiple copies observed in this study was not observed before.…”
Section: Discussioncontrasting
confidence: 72%
“…There is no published data on the prevalence of resistance markers to SP among pregnant in the studied area. However, compared to results from samples previously collected from children in the study area, the current study showed a higher prevalence in Pfdhfr SNPs at codons 51, 59 and 108 than in samples collected in 2004 (51-66%) [27] but similar to results of samples collected in 2013-2014 (92-95%) [26], whiles the Pfdhfr triple mutant IRN also showed a marked increase from 31% in 2004 [27] to 81% in the current study. Similar to samples collected in 2013-2014, Pfdhps K540E which was not detected in 2004 was present at low levels, but no A581G was detected in the current study.…”
Section: Plos Onesupporting
confidence: 67%
“…In Ghana, a few studies on SP resistance markers among pregnant women from different locations attending ANC showed IRN, IRN-SGKAA and IRN-SGEAA mutations covering a range from 71% to 80%, 12-41%, and 0-1% [23][24][25]. There are data for SP resistance markers in children resident in the forest-savannah zone of Ghana [26,27] but there are no published data on SP resistance markers in P. falciparum isolates obtained from pregnant women in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the location of breakpoints in areas of mono- or di-nucleotide repeats, encourage even more distinctive variations due to an AT-rich genome of P. falciparum . Nonetheless, there were minor exceptions, including in Cameroon, DRC, Kenya and Ghana [ 10 ], where both promoter and gene amplifications were present. Further, the extent of amplification copy number appears to be linked to geography.…”
Section: Discussionmentioning
confidence: 99%
“…Increased copy number of pfgch1 has been linked to SP resistance in Southeast Asia [ 8 ], with a direct association to pfdhfr and pfdhps alleles [ 9 ]. Similarly, a pfgch1 promoter copy number variation (amplification) in Malawian parasites with quintuple mutations (I51-R59-N108-G437-E540) has been identified, which differs from the whole gene amplification found in Southeast Asia [ 1 , 10 ]. The multiple copies of pfgch1 are thought to compensate for the putatively fitness-reducing mutations in pfdhfr and pfdhps by providing higher concentrations of upstream substrates in the folate-biosynthetic pathway [ 10 ].…”
Section: Introductionmentioning
confidence: 99%